HUBUNGAN MANUSIA DANLINGKUNGAN DALAM KARYA SENI LUKIS DENGAN GAYA FANTASI - Mubarak, Rifqi (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2015)
The purpose of making this research project are 1) to present the theme of humans and the environment are mutually beneficial and detrimental through painting. 2) ideas theme of human relationships and the environment through the power of imagination in works of fantasy art style. 3) produce works of art using the techniques of media Dussel with oil paint on canvas. Materials used in the making of this painting is the canvas, plamir, spanram, wood glue, wood paint, paint miyak, gasoline, and oil linsed. The tools used in creating this painting are paintbrush, palette, pencil, eraser, and a washcloth. Engineering works of art that authors use the technique of brushwork models Dussel and dry techniques. The process of creation of paintings in this research project through the stages of conceptualization of ideas in the form of search, data collection, material collection of images, and visualization in the form of making sketches on paper to paint on canvas. The size of the paintings varied authors study project, the two paintings measuring 60 cm x 80 cm, three paintings measuring 45 cm x 45 cm, and five paintings measuring 70 cm x 80 cm. The style used in making paintings are realist techniques with less fantasy style. Surrealistic subjects in this painting is the subject of imaginative fish, the human subjectÂ shell, bulb-headed human subject, the subject stems, sand human subjects and human subjects fish..